DIGITALIZATION OF LITERARY WORKS FOR TOURISM PROMOTION IN WEST SUMATRA, INDONESIA - Pratiwi, Dyani Prades; Hawa, Andina Meutia; Iman, Diah Tjahaya; Husna, Huriyatul; Ferdinal, Ferdinal (Universitas Islam Sumatera Utara (UISU), 2024)
Tourism literature establishes a reciprocal relationship between literature and tourism, with the digitization of literary works offering significant potential for tourism development. This research explores the use of digitalized literary works as a medium for promoting tourism in West Sumatra, Indonesia. Employing a qualitative descriptive method and a tourism literature approach, the study incorporates a literature review to analyze works related to West Sumatra. These are categorized into various forms of digitalized literature, including electronic books, audiovisual media, and films. The findings demonstrate that technological advancements expand the accessibility of literary works, reaching broader audiences and enhancing the potential for tourism promotion. Digital formats, such as videos shared on social media and films, provide imaginative portrayals of West Sumatra, transforming literary narratives into compelling visual experiences that highlight local tourist destinations. The study concludes that digitalization not only preserves the essence of literary tourism but also amplifies its impact by strengthening promotional strategies. By leveraging digitalized literary works, this approach is anticipated to attract more tourists and elevate the profile of West Sumatra as a vibrant cultural and tourism destination.